Problems and Ways of Solving in Translating the Diplomatic Case Study of “Prime Minister Zhou En-Lai Attending the Bandung Conference in 1955” - Chuenchoowes, Priya (Journal of Sinology (วารสารจีนวิทยา), 2008)
Problems and Ways of Solving in Translating the Diplomatic Case Study of “Prime Minister Zhou En-Lai Attending the Bandung Conference in 1995” The main objective of this research is to analyze the problems found in the process of translating from Chinese into Thai “ Prime Minister Zhou En-Lai attending the Bandung Conference in 1955 ”. Through translating “ Prime Minister Zhou En-Lai attending the Bandung Conference in 1955 “, this research has divided the problems into two main parts which are vocabulary level and sentence structure’s level. The methods proposed here are derived from many sources, such as the classroom, experiences and China’ s translation theory (Chinese-English) which are not yet well - known in Thailand.